2015
DOI: 10.1186/s11671-015-0911-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized zeolites as a perspective material for conductometric biosensors creation

Abstract: In this work, the method of enzyme adsorption on different zeolites and mesoporous silica spheres (MSS) was investigated for the creation of conductometric biosensors. The conductometric transducers consisted of gold interdigitated electrodes were placed on the ceramic support. The transducers were modified with zeolites and MSS, and then the enzymes were adsorbed on the transducer surface. Different methods of zeolite attachment to the transducer surface were used; drop coating with heating to 200°C turned ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For the first time, the efficiency of various types of zeolites as carriers for the enzyme immobilization has been shown when developing conductometric biosensors [2327]. The procedure of enzyme adsorption on silicalite was tested for a number of enzymes—acetylcholinesterase [27], urease [23, 25], recombinant urease [26], and butyrylcholinesterase [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, the efficiency of various types of zeolites as carriers for the enzyme immobilization has been shown when developing conductometric biosensors [2327]. The procedure of enzyme adsorption on silicalite was tested for a number of enzymes—acetylcholinesterase [27], urease [23, 25], recombinant urease [26], and butyrylcholinesterase [27].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of enzyme adsorption on silicalite was tested for a number of enzymes—acetylcholinesterase [27], urease [23, 25], recombinant urease [26], and butyrylcholinesterase [27]. Additionally, the effectiveness of this technique has been shown for enzyme biosensors based on pH-sensitive field-effect transistors [2832].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and overall performance of enzymatic biosensors has improved tremendously over the years as a result of the synthesis and incorporation of nanomaterials in their fabrication [ 2 , 3 , 4 , 5 ]. These materials have excited engineers due to their unique structural, electrical, chemical and mechanical properties [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the overuse of these pesticides results in pesticide residues in the environment. [21][22][23][24][25][26][27] Very recently, our research group has shown the selective detection of neurotransmitters dopamine and epinephrine using porous polyaniline (PANI) and polyaniline-zeolite composite modified electrodes with high activity and sensitivity compared to the conventional polyaniline modified electrode. 17 Our research is focused on the synthesis of nanostructured metal oxides, polyaniline, zeolites and their nanocomposites and finds their applications in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%